Analysis of Students’ Understanding of Motion Concept with Video based Learning Assisted by Tracker Software - Nur Utami Amaliah; I Wayan Darmadi; Sahrul Saehana (Berkala Ilmiah Pendidikan Fisika, 2020)
This study aims to determine and analyze students' understanding of the motion concept taught with video-based learning assisted by Tracker Software. The subjects of this descriptive qualitative research were 30 students from 10th grade at SMA Negeri 5 Palu. The instruments in this study were multiple-choice tests and interviewed guide. Multiple-choice tests are used with reasons and are equipped with a Specific Response Index (CRI). It was given before and after video-based learning assisted by Tracker Software applied. To add the information about students' understanding, the interview with a few respondents was done. Respondents were selected based on subjects' written test results in the high, medium, and low categories. They also were interviewed related to their conception and certainty of their answers. In learning by using video-assisted by tracker software, the student also employed the worksheet in experimenting. The results showed that a conceptual understanding of student motion on the initial test could be categorized as low. After using video media that is assisted by Tracker Software, students' conceptual understanding increases. Thus, the teacher can use video media and software to teach physics concepts that can be directly observed and displayed using mathematical and graphical representations.